The Role of Cynism and Affective Commitment in Mediating Empowering Leadership Style with Gender Bias Moderation on Subsorits’ Compliance Towards Female District Heads in District Governments across East Java - Sari, Novita; Suryanto, Bagong; ., Suryanto (Journal of Cultural Analysis and Social Change, 2025)
This study aims to analyze the role of cynicism and affective commitment in mediating the influence of empowering leadership style on subordinate compliance, with gender bias as a moderating variable, among female sub-district heads (camat) in East Java. The background of this research is rooted in the persistent gender stereotypes and discrimination that affect the legitimacy of women’s leadership in the public sector. The research employed a quantitative survey design, involving a population of 39 female sub-district heads and 285 subordinate respondents from 666 sub-districts across East Java, using a two-stage cluster sampling technique. The results of the study indicate that the direct influence of a leadership style that empowers female superiors on subordinate compliance is not significant or has not been proven to directly increase subordinate compliance, while the leadership style has a positive and significant influence on affective commitment, the higher the value of the leadership style, the higher the level of individual affective commitment, as well as subordinate cynicism. Although the empowering leadership style is successful in increasing affective commitment, it has not been proven to make subordinates more obedient to superiors, so it is unable to bridge the relationship between the empowering leadership style and compliance. There is a clear and significant indirect path, that the empowering leadership style affects subordinate compliance through the mechanism of reducing subordinate cynicism. This means that changes in compliance occur because empowering leadership changes the level of subordinate cynicism. Gender bias does not change how strong the influence of the empowering leadership style on affective commitment. Whether low or high gender bias, the effect of the empowering leadership style on effective commitment is more or less the same, as is the effect of cynicism which does not differ in conditions of high or low gender. The implications of this study highlight the importance of managing subordinate cynicism, increasing organizational transparency, and providing training for female leaders to integrate empowerment with role clarity and assertive communication. The theoretical contribution of this research enriches Social Exchange Theory (SET) by emphasizing cynicism as a critical mediator and gender bias as a complex moderator within the public bureaucracy context.